2000
DOI: 10.5432/jjpehss.kj00003397627
|View full text |Cite
|
Sign up to set email alerts
|

Development of ADL index for healthy older persons : proposal of useful ADL items and their scales

Abstract: The purpose of this study was to propose useful activities of daily living(ADLs)and scales for es − timating ADL ability in healthy older persons . The subjects were 210001der persons . A total of 130 items for 57 ADLs were selected from the following 4 domains: 10comotion , rnanipulation , stabnity , and posture − change . The achievenlent rate for each item was calculated . First , 15 more useful AI)Ls, consisting of 45 items , were selected to estimate ADL ability based on the multiple scale , considering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The ADL questionnaire was used to assess ADL (Sato et al, 2000). Its validity and reliability are being examined.…”
Section: ) Physical Qolmentioning
confidence: 99%
See 1 more Smart Citation
“…The ADL questionnaire was used to assess ADL (Sato et al, 2000). Its validity and reliability are being examined.…”
Section: ) Physical Qolmentioning
confidence: 99%
“…QOL Models for the Elderly with Purpose in Life and the Effect of Habitual Exercise were requested to select one from among three options for each question. Scoring depended on predetermined rules (Sato et al, 2000). Questions concerning self-evaluation of physical fitness and health were as follows (numbers in parentheses indicate scores given to individual categories).…”
mentioning
confidence: 99%
“…This survey consists of four domains: locomotion (walking, running, jumping across a ditch, ascending and descending stairs, and convey), posture change (sitting up and standing up from the floor), stability (standing on one foot with eyes open, standing in a bus or a train, and dressing while standing), and manipulation (buttoning a shirt and placing a Japanese mattress into and removing it out of a closet), and the degree of achievement of ADLs required for independent life was evaluated according to these 12 items [4, 5]. Each item consisted of three different difficulty levels, with subjects selecting the appropriate level for each ADL item.…”
Section: Methodsmentioning
confidence: 99%
“…Demura and Sato [3] reported that the ability to live independently should be assessed in the elderly. In addition, Sato et al [4] reported that the ability to achieve activities of daily living (ADLs), rather than the ability to perform physical functions at maximum exertion, should be assessed for the elderly. In brief, it is important for the elderly to retain the ability to achieve ADLs at above a certain level to maintain an independent daily life [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…The ADL consists of four domains: locomotion, manipulation, stability, and posture change [23,24]; the ability to perform these motions is important for the elderly to maintain an independent daily life. Manipulation motions mainly use the upper limbs, but the other three motions are significantly affected by movements of the knee joint.…”
Section: Introductionmentioning
confidence: 99%